The PERKEMBANGAN EKONOMI KREATIF DALAM MENOPANG PEREKONOMIAN PASCA PANDEMI COVID-19 DI KABUPATEN BULELENG: Pembangunan, Ekonomi Kreatif, Ekonomi - I Putu Gede Diatmika; I Wayan Krisna Eka Putra (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The creative economy is considered a new force, Indonesia sees developments after the Covid-19 pandemic. Therefore, the creative economy must be developed in a sustainable manner by strengthening all aspects such as resources, industry, financing, marketing, technology and infrastructure.To develop the creative economy in supporting the post-Covid-19 economy, there are several problems, including; The development of creative industries is not yet optimal, mainly due to the lack of industrial attractiveness, the existence of a dominant position for creative businesses, the immature creative industry business model, and the business risks that must be faced; The development of creative economic resources is not yet optimal. The purpose of this study is to describe the potential of creative industries and describe creative economic resources in supporting the post-Covid-19 economy in Buleleng Regency. The research method uses a mix method approach (descriptive qualitative and quantitative). Methods of data collection in this study were carried out by observation (field observation), surveys (field surveys), and interviews (interview method). The results showed that the coefficient of determination obtained from the Adjusted R Square value was 0.893 or 89.3 percent. This means that the variables of creative economic potential and creative economic resources have a significant positive influence on the development of the creative economy in supporting the economy in Buleleng District after the Covid-19 pandemic by 89.3 percent.